Influence of weather conditions on the yield and quality of spring wheat grain in the forest-steppe of the Middle Volga region - I. F. Demina (Аграрная наука Евро-Северо-Востока)
The purpose of the research is to evaluate the influence of weather factors in 2016-2021 on the yield and quality of grain of 18 varieties and 28 lines of spring soft wheat of competitive variety trial in the conditions of forest-steppe of the Middle Volga (Penza region). To characterize the meteorological conditions, the average daily air temperatures, precipitation and hydrothermal coefficient (HTC) were taken. In the analysis of grain quality, the content of protein and gluten in the grain, as well as flour strength, quality indexes of the variety and farinograms of the dough were used. The result of the research stated the negative correlation between the yield and air temperature in June r = -0.518±0.128 («booting» phase), in August it was slightly weaker r = -0.342±0.141. Correlations of the yield with precipitation and HTC were positive. The average significant correlation of the yield was formed with precipitation and HTC in June: r = 0.509±0.130 and r = 0.552±0.126, respectively. A significant negative correlation was found between the yield and protein and gluten content in the grain: r = -0.758±0.098 and r = -0.782±0.094. The content of protein and gluten in the grain were almost functionally dependent on each other – r = 0.945±0.055. A high positive correlation has developed between the content of protein and gluten in the grain with the average daily air temperature in the second half of the growing season in July r = 0.845±0.081 and 0.902±0.065, in August: r = 0.858±0.080 and 0.898±0.075, respectively. Positive weak correlation was found between the yield and flour strength, variety quality indices and dough farinograms (r = 0.354±0.148, 0.402±0.138 and 0.423±0,136), respectively. Precipitation and a high rate of HTC in the second half of the growing season reduced the quality indices of the variety and farinograms of the dough, the strength of the flour. This dependence was characterized by a weak negative relationship: from r = -0.310±0.144 to r = -0.458±0.134. Thus, the formation of yield and quality indicators of grain of spring soft wheat is influenced by the temperature regime and the amount of precipitation in all phases of growth and development of plants.